Search for Superconductivity in Micrometeorites - Guénon, S. (Sci Rep, 2014)
We have developed a very sensitive, highly selective, non-destructive technique for screening inhomogeneous materials for the presence of superconductivity. This technique, based on phase sensitive detection of microwave absorption is capable of detecting 10(−12) cc of a superconductor embedded in a non-superconducting, non-magnetic matrix. For the first time, we apply this technique to the search for superconductivity in extraterrestrial samples. We tested approximately 65 micrometeorites collected from the water well at the Amundsen-Scott South pole station and compared their spectra with those of eight reference materials. None of these micrometeorites contained superconducting compounds, but we saw the Verwey transition of magnetite in our microwave system. This demonstrates that we are able to detect electro-magnetic phase transitions in extraterrestrial materials at cryogenic temperatures.